Imatinib as a potentially effective therapeutic alternative in corticosteroid‐resistant eosinophilic fasciitis. Issue 6 (24th September 2020) - Wu, Tiffany T.; Goodarzi, Heidi; Wang, Jennifer; Novoa, Roberto; Teng, Joyce M. C.
Abstract: Eosinophilic fasciitis (EF) is a rare condition in children that is typically treated with systemic corticosteroids. We present the case of a 9‐year‐old boy with biopsy‐proven EF, refractory to systemic corticosteroids and methotrexate. The tyrosine kinase inhibitor imatinib was added as adjuvant therapy, leading to improvement in joint function and skin laxity. Our case is the first to suggest the anti‐fibrotic properties of imatinib may benefit EF patients.